MIND OVER CRISIS: EXPLORING COVID-19 IMPACT ON MENTAL HEALTH AND THE PATHWAY TO RESILIENCE - 1. Dr.P.Nathiya , 2. Silpa Meenakshi V (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The COVID-19 pandemic has significantly impacted global life, disrupting various aspects, including adolescent psychological well-being. This paper examines how the pandemic affected adolescents, a group facing unique developmental challenges. Understanding these effects is crucial, as mental health concerns among adolescents often receive less attention in broader public health discussions. The study explores disruptions in daily routines, increased mental health challenges, academic stress, strained social relationships, and shifting family dynamics. Additionally, it examines coping mechanisms, resilience, long-term psychological consequences, and interventions to support adolescent well-being. Through a comprehensive review of existing research, the paper synthesizes findings on adolescent mental health during COVID-19. The results reveal heightened levels of anxiety, depression, loneliness, and social isolation. Online learning transitions, cancelled extracurricular activities, and family conflicts have further intensified stress, affecting self-esteem. This study highlights the need for early intervention and emphasizes the role of schools, communities, and government programs in providing mental health support. Ultimately, the findings call for continued research and policy initiatives to mitigate long-term effects and ensure adolescent psychological well-being during and beyond future crises.